Dampak Konsumerisme berupa Judi Online di Indonesia: Perspektif Ekonomi, Sosial, dan Mental - Syakira, Nafis Azka; Ramadhahana, Naila Fathma; Anggita, Nayla Devi; Tsaqifa, Tazkia; Husna, Rystia Naila (Interaktif : Jurnal Ilmu-Ilmu Sosial, 2024)
Online gambling consumerism in Indonesia has increased rapidly along with technological advances and wider internet access. This study aims to analyze the impact of online gambling consumerism from economic, social, and mental perspectives. From an economic perspective, online gambling can bring financial benefits to platform providers, but it also has negative consequences such as loss of community income and increased economic burden due to irresponsible gambling. Socially, this phenomenon has the potential to damage family structures, increase crime rates, and create social stigma for gambling addicts. From a mental perspective, online gambling can trigger addiction, depression, and other mental disorders, resulting in a decline in the quality of life of individuals. Researchers used quantitative methods by surveying 30 people. This study provides insight into the challenges faced by individuals and society related to online gambling consumerism and suggests the need for more effective social interventions and public policies to address this issue. With a better understanding of these impacts, it is hoped that appropriate mitigation efforts can be carried out to create a healthier and more prosperous society. Keywords: Consumerism, Online Gambling, Impact of Online Gambling, Impact of Consumerism